A Fragment of the Mythological Discourse of the Pagan Slavs in Orthodox Literature - Łuczyński, Michał (Respectus Philologicus, 2012)
Textual reconstruction is a very peculiar linguistic discipline and, although scores of scientific publications profess to deal with it, there are still not many theoretical works dealing with its methodological foundations. In a number of works published since the early 1960s, several Russian linguists of the semiological school of Tartu University – V. V. Ivanov and V. N. Toporov – have developed a distinctive approach to textual reconstruction. Their hypothesis of the “basic myth,” as they call the Slavic myth about the duel of the Thunder God (*Perunъ) and his adversary (*Velesъ), is based on the comparative and structural analysis of a huge number of historical and folk texts of many traditions, as well as on typological confirmations and binary interpretations. Linguists such as T. M. Sudnik, T. V. Civ’jan and R. Katičić have been strongly influenced by this school. Actually, these elements are not found in the works of Radoslav Katičić, who has contributed a reconstruction of Balto-Slavic texts connected with pagan fertility rites as correlated with the myth of an incestuous marriage between the son of the Storm God and his sister; however, the way he uses folklore material owes a lot to Ivanov and Toporov.The author of this work focuses on the problem of the possibility of reconstructing mythological discourse as a method of paleolinguistic research. This paper is intended as a synthetic overview of one of the neglected topics of textual reconstruction – the intertextual analysis of literary Old Russian texts. The article is centred on the reconstruction of a fragment of pagan oral discourse on the basis of homiletic and paranetic literature. The result – a fragment of the myth about the Slavic god called *Rodъ – is compared with the theory of Indo-European textual reconstruction on the syntactic and paradigmatic levels and their corresponding contexts in various common Slavic languages. The article aims to use and examine theoretical ideas of this branch of Indo-European linguistics in a practical study of a text and its transformations.
Keywords: discourse; textual reconstruction; intertextuality; Slavic studies; Old Russian literature; Slavic mythology